REPRESENTASI KECANTIKAN PEREMPUAN DALAM IKLAN POND’S “Perfecting Cream Ft Maudy Ayunda” - Ade Dianasari, Kadek Ayu; Purnawan, Ni Luh Ramaswati; Pradipta, Ade Devia (E-Jurnal Medium, 2021)
In the context of marketing, advertising is the spearhead in supporting the marketing success of a product and service. Through images or ideas that have been created, advertisement are expected to be able to persuade consumers to consume the product and service that have been advertised. In the case of binding to the public’s attractiveness, the female figure is often used as a symbol to display the visual form of the audience. The representation of female beauty that the marketing have made generaly establish a standard of certain beauty such as tall, have a white skin and straight hair. But now, advertising has also undergone a change as in the Pond’s Perfecting Cream Ft. Maudy Ayunda advertisement. Through qualitative research with Charles Sander Peirce’s semiotic analysis method, the results obtained that representations of female beauy can not be judged by one standard of beauty, but it is diverse.   Key Words : Television Advertising, Representation of Female Beauty, Semiotics.